Diagnostic Accuracy of 256-Detector Row Computed Tomography in Detection and Characterization of Incidental Pancreatic Cystic Lesions. (2nd June 2015) - Ippolito, D.; Allegranza, P.; Bonaffini, P. A.; Talei Franzesi, C.; Leone, F.; Sironi, S.
Abstract : Purpose . To assess the diagnostic value of 256-detector row MDCT in the characterization of incidentally detected pancreatic cystic lesions (PCLs). Materials and Methods . We retrospectively reviewed 6389 studies performed on a 256-row detector scanner, wherein ≥1 PCLs were incidentally detected. Images from a total of 192 patients (99 females; age range 31–90 years) were analysed referring to morphologic predictive signs of malignancy, including multifocality, inner septa, wall thickening, and mural enhancing nodules. Results . We evaluated 292 PCLs in 192 patients (solitary in 145 and ≥2 in 47; incidence 2.05%). Size ranged from 3 to 145 mm (mean 15 mm); body was the most common location (87/292; 29.8%). Intralesional septa were detected in 52/292 lesions (17.8%), wall thickening >2 mm in 13 (4.5%), enhancing wall and mural nodules in 15 (5.1%) and 12 (4.1%), respectively. Communication with ductal system was evident in 45 cases. The most common diagnoses, established by histology or imaging analysis, were IPMNs (about 86%), while serous cystic neoplasia (3.7%) and metastases (0.5%) were the less common. Conclusion . MDCT provides detailed features for characterization of PCLs, which are incidentally discovered with increased frequency due to the widespread use of cross-sectional imaging.